Myopotential Inhibition of Demand Pacemakers - Lazar, Anthony V. (1982)
Two patients are described in whom skeletal muscle potentials originating in the shoulder girdle muscles during isometric movement suppressed the discharge of a ventricular demand unipolar pacemaker, resulting in syncope. Converting the pulse generator into a fixed-rate mode with the magnet prevented the inhibition. Improved filters or wider use of bipolar electrodes should prevent this form of interference.